Low‐Temperature Solution Crystallization of Nanostructured Oxides and Thin Films. Issue 42 (13th July 2020) - Bretos, Iñigo; Diodati, Stefano; Jiménez, Ricardo; Tajoli, Francesca; Ricote, Jesús; Bragaggia, Giulia; Franca, Marina; Calzada, Maria Lourdes; Gross, Silvia
Abstract: As an introduction to this themed issue, a critically selected overview of recent progress on the topic of solution methods for the low‐temperature crystallization of nanoscale oxide materials is presented. It is focused on the low‐temperature solution processing of oxide nanostructures and thin films. Benefits derived from these methods span from minimizing the environmental impact to reducing the fabrication costs. In addition, this topic is regarded as a key objective in the area because it offers a unique opportunity for the use of these materials in areas like flexible electronics, energy conversion and storage, environmental sciences, catalysis, or biomedicine. Abstract : Towards room temperature crystallization : This progress report provides a critically selected overview of the recent progress on solution methods for the crystallization at low temperatures of nanoscale oxide materials in the form of both nanoparticles and thin films. The most relevant solution strategies reported in the literature are concisely reviewed and forthcoming novel developments in the field are outlined.